Provision of physiotherapy rehabilitation following neck dissection in the UK. Issue 7 (13th June 2018) - Robinson, M; Ward, L; Mehanna, H; Paleri, V; Winter, S C
Abstract: Background: Neck dissection is associated with post-operative shoulder dysfunction in a substantial number of patients, affecting quality of life and return to work. There is no current UK national practice regarding physiotherapy after neck dissection. Method: Nine regional centres were surveyed to determine their standard physiotherapy practice pre- and post-neck dissection, and to determine pre-emptive physiotherapy for any patients. Results: Eighty-nine per cent of centres never arranged any pre-emptive physiotherapy for any patients. Thirty-three per cent of centres offered routine in-patient physiotherapy after surgery. No centres offered out-patient physiotherapy for all patients regardless of symptoms. Seventy-eight per cent offered physiotherapy for patients with any symptoms, with 11 per cent offering physiotherapy for those with severe dysfunction only. Eleven per cent of centres never offered physiotherapy for any dysfunction. Conclusion: The provision of physiotherapy is most commonly reactive rather than proactive, and usually driven by patient request. There is little evidence of pre-arranged physiotherapy for patients to treat or prevent shoulder dysfunction in the UK.